Applying sequence methods to the study of team temporal dynamics. (November 2015) - Herndon, Benjamin; Lewis, Kyle
In this paper, we explain how structuring, characterizing, and analyzing team experience in terms of temporal sequences can yield new insights about the dynamic nature of teams. We suggest that sequence methods can offer a fuller representation of team temporal dynamics than is typically possible with cross-sectional or longitudinal multiphase designs alone. We provide suggestions for how to use sequence methods to develop teams research questions and conduct sequence analysis. To make our suggestions more concrete, we develop detailed examples that highlight the potential for sequence methods to advance the study of team temporal dynamics by augmenting conventional methods.